Competition between Hydrogen Evolution and Carbon Dioxide Reduction on Copper Electrodes in Mildly Acidic Media - Ooka, Hideshi; Figueiredo, Marta C; Koper, Marc T M (Langmuir, 2017)
Understanding the competition between hydrogen evolution and CO reduction is of fundamental importance to increase the faradaic efficiency for electrocatalytic CO reduction in aqueous electrolytes. Here, by using a copper rotating disc electrode, we find that the major hydrogen evolution pathway competing with CO reduction is water reduction, even in a relatively acidic electrolyte (pH 2.5). The mass-transport-limited reduction of protons takes place at potentials for which there is no significant competition with CO reduction. This selective inhibitory effect of CO on water reduction, as well as the difference in onset potential even after correction for local pH changes, highlights the importance of differentiating between water reduction and proton reduction pathways for hydrogen evolution. In-situ FTIR spectroscopy indicates that the adsorbed CO formed during CO reduction is the primary intermediate responsible for inhibiting the water reduction process, which may be one of the main mechanisms by which copper maintains a high faradaic efficiency for CO reduction in neutral media.